Molecular epidemiological typing of emerging methicillin-resistant Staphylococcus aureus strains in the community, among livestock and in healthcare facilities in Ireland, 2001-2015 - Brennan, Gráinne I. (Trinity College (Dublin, Ireland). Dublin Dental University Hospital. Division of Oral Biosciences, 2017)
Methicillin-resistant Staphylococcus aureus (MRSA) has been endemic in Irish hospitals for four decades and displacement of predominant clones has occurred several times. Sequence type (ST) 22 carrying staphylococcal cassette chromosome (SCC) mec type IV has predominated in Irish healthcare facilities (HCF) since 2002. In recent years, an increase in sporadically-occurring non-ST22-MRSA-IV from bloodstream infections (BSIs) was observed indicating that strain displacement may occur again. Elsewhere, sporadically-occurring strains recognised in Ireland have emerged as predominant strains in HCFs. The first part of this study undertook an in-depth molecular characterisation of 276 sporadically-occurring MRSA isolates from patients attending Irish hospitals, general practitioners (GP) and a veterinary laboratory from 2001-2015. All isolates underwent antimicrobial susceptibility testing (AST), spa typing and DNA microarray profiling to investigate the genetic backgrounds, SCCmec-associated genes and antimicrobial resistance and virulence genes. The 276 isolates were assigned to 86 spa types, 14 multilocus sequence typing (MLST) clonal complexes (CC), 11 STs and 18 combinations of SCCmec genes. Combining the CCs and SCCmec types resulted in 48 different type combinations. Community associated (CA), livestock associated (LA) and healthcare-associated (HCA) MRSA lineages were identified including CC1-MRSA-IV (22.5%, 62/276) & CC5-MRSA-V (8.3%, 23/276), CC398-MRSA-V (3.6%, 10/276) & CC130-MRSA-XI (0.4%, 1/276) and ST239-MRSA-III (1.8%, 5/276), respectively. Common virulence genes included the immune evasion cluster (IEC) (86.6%, 239/276), the enterotoxin gene cluster (egc; 46.7%, 129/276) and enterotoxin genes sek/q (13.0%, 36/276) and seh (26.8%, 74/276). The isolates harboured multiple resistance genes including those encoding resistance to beta-lactams (blaZ/blaZxi, 96%, 264/276), macrolides (erm(A), erm(B), erm(C), lnu(A) and/or mph(C), 59.8%, 165/276), aminoglycosides (aacA-aphD, aadD and/or aphA3, 43.2%, 119/276) and tetracycline (tet(K) and/or tet(M), 25.0%, 69/276), as well as the SCCmec/SCC-encoded fusidic acid resistance gene fusC (19.2%, 53/276). Several nosocomial outbreaks caused by CA-MRSA lineages were investigated, including two by pvl-positive ST772-MRSA-IV, one by CC1-MRSA-IV and one by CC5-MRSA-V. These isolates harboured multiple resistance and virulence genes. In the case of one ST772-MRSA-IV outbreak, a healthcare worker (HCW) who had recently been hospitalised in India where this strain predominates subsequently transmitted the strain to babies in a neonatal intensive care unit in Ireland. This highlights the need for MRSA screening of HCWs and of the threat posed by the spread of pvl-positive CA-MRSA into hospitals. Livestock-associated CC398 MRSA were also identified (n = 12) which along with an additional nine CC398 MRSA and 10 CC398 methicillin susceptible S. aureus (MSSA) were further investigated. The CC398 MRSA harboured SCCmec IVa or VT, exhibited spa type t011 or t034 and carried different combinations of multiple resistance genes including those encoding resistance to erythromycin, tetracycline, spectinomycin and aminoglycosides. Four distinct incidents of CC398 MRSA were identified, including the transmission of CC398 from a veterinarian with recent travel to Belgium to a horse and between pigs (n = 9) and farm workers (n = 9) on two farms, one of which had been restocked with gilts from Germany. These findings have significant implications for human and animal health and the Irish agricultural industry …
Keywords: Dental Science, Ph.D.; Ph.D. Trinity College Dublin